An Empirical Exploration of Sports Sponsorship: Activation of Experiential Marketing, Sponsorship Satisfaction, Brand Equity, and Purchase Intention - Hsiao, Chun-Hua; Tang, Kai-Yu; Su, Yu-Sheng (Frontiers in Psychology, 2021)
The purpose of this study is to investigate the relationship between the activation of experiential marketing, satisfaction with sponsored sporting events, brand equity, and subsequent product purchase intentions in a small-scale sponsorship campaign. Survey data were collected from 238 actual runners in the terminal rest area after they had completed a race. Structural equation modeling with bootstrap method was carried out to examine the proposed hypotheses. Results revealed that in terms of product purchase intention, brand equity was the most influential factor, followed by experiential marketing activation and satisfaction with the sponsorship. Specifically, experiential marketing activation significantly influenced the sports sponsorship and the sponsor’s brand equity; however, satisfaction showed an insignificant effect on purchase intention. In addition, the mediation test shows that brand equity is an important mediator of experience marketing and satisfaction to product purchase intention. Findings provide some empirical insights into how small-scale sponsorship can benefit sponsoring companies, including intangible brand assets and tangible product consumption. The results could encourage more companies to organize small-scale sponsorship races and to present brand-related experiences (e.g., experiencing product packaging, on-the-spot experience areas). In this way, opportunities may be provided to attract more runners (or potential consumers) to participate in the event and have a deeper brand experience. This study contributes to a better understanding of the effectiveness of small-scale sponsorship in Asia to increase the generalization of the small sponsorship literature.